ON THE WAY TO UNITY: POLISH EDUCATORS AND UKRAINIAN TEACHERS IN THE PROCESS OF MODERN EDUCATION AND TRAINING - Sliverskyi, Boguslaw (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article of Bohuslav Slivhersky "Polish teachers together with Ukraine" is dedicated to Polish-Ukrainian ties in general and scientific, scientific and pedagogical ties in particular. The author of the article, being for a long time the head of the Committee of Pedagogical Sciences of the Polish Academy of Sciences, has long been maintaining creative relations with the scientific community of Ukraine, in particular, with the leadership of the National Academy of Pedagogical Sciences of Ukraine, monitors and comments in his blog social, scientific, cultural and educational, etc. events and phenomena that take place in Ukrainian society. The last two years of his publications have been devoted to the heroic struggle of the Ukrainian people against the Moscow occupier, who treacherously attacked Ukraine on February 24, 2022. The article analyzes various events that take place in modern Ukraine, and much attention is paid to Ukrainian refugees living in Poland, the education of Ukrainian children in Polish schools and so on. The purpose of the article is to show the cooperation of Polish and Ukrainian scientists in the field of pedagogical science, assistance of the Republic of Poland to Ukrainian citizens during the brutal Russian-Ukrainian war, various Polish-Ukrainian ties in political, economic, scientific, social, cultural and educational and other fields. Research methods. The main method used by the author is the method of observation, fixation and description of various facts and events that have occurred in Ukraine recently. Scientific novelty. The Polish media has many materials dedicated to Ukraine, but this article presents a scientific analysis of the events of the last two years, the ideas and views of scientists of the two countries concerning the war in Ukraine are highlighted, which was not done before.